Mapping the literature on parent-child language across activity contexts: a scoping review. Issue 1 (2nd January 2022) - Holme, Caitlin; Harding, Sam; Roulstone, Sue; Lucas, Patricia J.; Wren, Yvonne
ABSTRACT : Linguistic interactions between parents and their children are frequently studied to investigate how children acquire language. From observations, researchers have identified interaction strategies that foster children's language development. In turn, interventions to support children's early language skills employ styles of interaction derived from these observations. However, researchers have not often considered how the activity context selected for observation may affect the language used, or whether these contexts reflect children's diverse experiences. The aim of this scoping review was to explore the breadth of literature about language use across a range of activities. Included studies described linguistic outputs of parents and typically developing children (aged 1;0–5;11 years) and activity context(s). Searches were conducted in PsycInfo, Medline, CINAHL, ERIC-ProQuest and Google Scholar. From 16, 718 records, 59 studies were retained. Studies were charted according to the population included, linguistic outputs recorded, activity contexts studied and the methodological design. To allow for comparison of results across activity contexts, five thematic categories were identified: play activities, book reading, naturalistic routines, media and methodological implications. Challenges for future research are discussed, including ways to ensure the ecological validity of findings by coupling naturalistic language recordings with data collected during diverse everyday activity contexts.